TURTLE CONSERVATION IN SERANGAN ISLAND: THE IMPLEMENTATION OF COMMUNITY-BASED TOURISM CONCEPTS IN TOURISM DEVELOPMENT - I Made Darma Oka; Putu Widya Darmayanti; I Wayan Sonder (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
This paper discusses the implementation of community-based tourism (CBT) concepts in tourism development of the turtle conservation in Serangan Island, Bali, Indonesia. The data were collected through observation, interview, library research, and focus group discussion. The informant was determined using the sampling purposive method. The data were descriptively and qualitatively analyzed. The result of the study shows that the community-based tourism concepts were implementation in turtle conservation to inspire the local people to more actively participate in conserving turtles. The CBT concepts were applied to the turtle conservational program; they are community participation, natural conservation, socio-cultural conservation, and economic benefit.